EFFECTIVE TECHNOLOGY OF DEVELOPING LEARNERS’ CRITICAL THINKING SKILLS - Z. Tukhtasinova (Galaxy International Interdisciplinary Research Journal, 2022)
The technology created on the basis of E. de Bono’s “Six Thinking Caps” theory, aimed at developing students’ critical thinking, and its application in English language education are highlighted in this article.